The Ability of Near-Infrared Autofluorescence to Protect Parathyroid Gland Function During Thyroid Surgery: A Meta-Analysis - Wang, Bin; Zhu, Chun-Rong; Liu, Hong; Yao, Xin-Min; Wu, Jian (Frontiers in Endocrinology, 2021)
Objective We conducted this meta-analysis to assess the ability of near-infrared autofluorescence to protect parathyroid gland function during thyroid surgery. Method A systematic literature search was conducted using PubMed, Embase, and the Cochrane Library electronic databases for studies published up to February 2021. The reference lists of the retrieved articles were also reviewed. Two authors independently assessed methodological quality and extracted the data. A random-effects model was used to calculate the overall pooled variable and the weighted mean deviation. Publication bias in these studies was evaluated using the Egger’s and Begg’s tests. Result Seven studies involving 1,480 patients were included in the analysis. Compared with patients in the naked eye group, the pooled relative risk of inadvertent parathyroid gland resection and parathyroid gland autotransplantation for the patients in the near-infrared autofluorescence group was 0.48 (95% CI, 0.26–0.9, p = 0.023) and 0.39 (95% CI, 0.09–1.68, p = 0.208), respectively. The pooled relative risk of hypocalcemia at 1 day postoperatively and at 6 months postoperatively for the patients in the near-infrared autofluorescence group was 0.49 (95% CI, 0.34–0.71, p < 0.001) and 0.34 (95% CI, 0.06–2.03, p = 0.238) compared with patients in the naked eye group. Conclusion Near-infrared autofluorescence is significantly associated with a reduced risk of inadvertent parathyroid gland resection and hypocalcemia at 1 day postoperatively.